2018
DOI: 10.1007/s11427-018-9322-6
|View full text |Cite
|
Sign up to set email alerts
|

A combination of follicle stimulating hormone, estradiol and age is associated with the pregnancy outcome for women undergoing assisted reproduction: a retrospective cohort analysis

Abstract: To investigate the effect of basal hormone levels including follicle stimulating hormone (FSH) and estradiol (E) and age on the pregnancy outcomes in women undergoing in vitro fertilization and embryo transfer (IVF-ET), we designed a retrospective cohort analysis and collected information of patients undergoing IVF between January 2014 and April 2017. We found that young women had much better pregnancy outcomes than older women regardless of the hormone levels. The pregnancy outcomes declined in young women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Some studies also suggested that the FSH level on cycle day 3 was a better indicator of IVF outcome than female age [24]. High levels of basal E2 level were associated with low oocyte yields, low pregnancy rates and higher cancellation rate independent of FSH levels [25,26]. Our results are consistent with the above studies.…”
Section: Strengths and Weaknessessupporting
confidence: 91%
“…Some studies also suggested that the FSH level on cycle day 3 was a better indicator of IVF outcome than female age [24]. High levels of basal E2 level were associated with low oocyte yields, low pregnancy rates and higher cancellation rate independent of FSH levels [25,26]. Our results are consistent with the above studies.…”
Section: Strengths and Weaknessessupporting
confidence: 91%
“…Women generally reach peak reproductive potential well before the age of 30 and then experience a slow decline in reproductive potential until the age of 40, at which point the decline becomes more precipitous [18]. Although IVF-ET is the most effective treatment for women who are > 40 years old [15], the success rate for older women is still very low [16]. It is commonly known that fertility decreases with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that, compared with young patients, older patients showed significantly decreased numbers of retrievable oocytes and available embryos and had a lower clinical pregnancy rate after assistant reproductive technology. In addition, we compared the final outcomes between young and old pregnant women and found that older women have significantly increased miscarriage rates and decreased live birth rates [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations